The Impact of Servant Leadership Style on Team Cohesiveness: "A field study on Syrian Telecom Company" (Damascus University Journal for the economic and Political sciences, 2026)
The research aimed to study the impact of servant leadership on team   on team cohesiveness Syrian Telecom Company,. the research relied on the positivism philosophy ,the deductive method and quantitative approach  by using  the questionnaire tool. 225 questionnaires were distributed and 209 questionnaires were retrieved from them that can be analyzed using the SPSS program. The research reached results, The most important of which are all the dimensions of servant leadership and the cohesion of the work teams, which are present and achieved for the study sample in the Syrian Telecommunications Company. The study showed that there is a significant effect for all dimensions of servant leadership on the cohesion of the work teams in the telecommunications company. There are also no statisticallysignificant differences in the level of evaluation and availability of the dimensions of servant leadership depending on The demographic variables of the study sample in terms of gender, academic qualification, and years of experience, while there are statistically significant differences in the level of evaluation and availability of dimensions of administrative leadership depending on the demographic variables of the study sample in terms of age group. The study presented a set of recommendations including raising in the level of application of all dimensions of servant leadership of the employees of the Syrian telecom company because of its significant Impact on the team cohesiveness with the need to focus primarily on the leader acting ethically with his employees, then his altruism and also playing his role to empower his employees.
Keywords: Servant Leadership; Team Cohesion; Syrian Telecom Company